Impact of cardiac surgery associated acute kidney injury on 1-year major adverse kidney events - Molina Andújar, Alícia; Escudero, Victor Joaquin; Piñeiro, Gaston J.; Lucas, Alvaro; Rovira, Irene; Matute, Purificación; Ibañez, Cristina; Blasco, Miquel; Quintana, Luis F.; Sandoval, Elena; Sánchez, Marina Chorda; Quintana, Eduard; et al. (Frontiers in Nephrology, 2023)
Background: the incidence of acute kidney injury following cardiac surgery (CSA-AKI) is up to 30%, and an increased risk of chronic kidney disease has been found when compared to AKI-free population. The aim of our study was to assess the risk of Major Adverse Kidney Events (25% or greater decline in eGFR, new hemodialysis, and death [MAKE]) after cardiac surery in a Spanish cohort and to evaluate the utility of the score developed by Legouis D et al (CSA-CKD score) in the prediction of MAKE. Methods: unicentric retrospective study of patients that required cardiac surgery with cardio-pulmonary bypass (CPB) during 2015 with one-year follow-up after intervention. The inclusion criteria were: patients over 18 years old who were operated on for cardiac surgery (valve substitution [VS], Coronary Artery Bypass Graft [CABG] or a combination of both procedures. Results: the number of patients with CKD (eGFR <60 ml/min) increased from 74 (18.3%) to 97 (24%) one year after surgery. Median eGFR declined from 85 to 82 ml/min in the no-CSA-AKI patients and from 73 to 65 ml/min in those who suffered CSA-AKI (p=0.024). Fifty-eight patients (14.4%) presented one-year MAKE. Multivariate logistic regression analysis showed that the only variable associated with MAKE was CSA-AKI (OR 2.386 [1.31-4.35], p=0.004). Median CSA-CKD score was higher in the MAKE cohort (3 [2-4] vs 2[1-3], p<0.001), but discrimination was poor, with AUC of 0.682 (0.611-0.754). Conclusion: CSA-AKI of any stage is associated with one-year MAKE. Further Research to disclose new scores that identify patients at risk are needed to provide appropiate follow-up.